2019
DOI: 10.1038/s41588-019-0518-4
|View full text |Cite
|
Sign up to set email alerts
|

Resequencing of 414 cultivated and wild watermelon accessions identifies selection for fruit quality traits

Abstract: Fruit characteristics of sweet watermelon are largely the result of human selection. Here we report an improved watermelon reference genome and whole-genome resequencing of 414 accessions representing all extant species in the Citrullus genus. Population genomic analyses reveal the evolutionary history of Citrullus, suggesting independent evolutions in Citrullus amarus and the lineage containing Citrullus lanatus and Citrullus mucosospermus. Our findings indicate that different loci affecting watermelon fruit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
258
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 258 publications
(270 citation statements)
references
References 76 publications
11
258
1
Order By: Relevance
“…And the unchanged nucleotide sequence of the cDNA, gDNA, and about 2,000bp bases before gene Cla97C04G068460 in WT4 according to the resequecing result further confirmed that gene Cla97C04G068460 would not be the gene for Clyr. With GWAS analysis, three candidate genes associated with rind color and rind stripe were found on chromosomes 4, 6, and 8, corresponding to the rind trait loci S (foreground stripe pattern), D (depth of rind color), and Dgo (background rind color) (Park et al, 2016;Guo et al, 2019). Since Dgo gene (Cla97C04G068530/Cla002769) encodes a magnesium-chelatase subunit H involved in chlorophyll synthesis, which was not mapped in the candidate region, so the relationship between Dgo and yellow-rind trait in WT4 should be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…And the unchanged nucleotide sequence of the cDNA, gDNA, and about 2,000bp bases before gene Cla97C04G068460 in WT4 according to the resequecing result further confirmed that gene Cla97C04G068460 would not be the gene for Clyr. With GWAS analysis, three candidate genes associated with rind color and rind stripe were found on chromosomes 4, 6, and 8, corresponding to the rind trait loci S (foreground stripe pattern), D (depth of rind color), and Dgo (background rind color) (Park et al, 2016;Guo et al, 2019). Since Dgo gene (Cla97C04G068530/Cla002769) encodes a magnesium-chelatase subunit H involved in chlorophyll synthesis, which was not mapped in the candidate region, so the relationship between Dgo and yellow-rind trait in WT4 should be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the selection of ClVST1, we analyzed the haplotype of ClVST1 and identified that the SNP C99A is the nonsynonymous mutation most associated with sugar content in a collection of 326 wild and cultivated watermelon accessions (Guo et al, 2019), with all nonsweet watermelons harboring the allele CC ). Yellow and red fluorescence indicates plasma membrane and chloroplast in leaf protoplasts, respectively (g).…”
Section: Discussionmentioning
confidence: 99%
“…The SNPs from 326 representative watermelon accessions (Guo et al, 2019) were used for nucleotide diversity (p) calculation using a 50 kb sliding window. We calculated the ratio of diversity (p semi-wild /p cultivated ) for each window using VCFTOOLS (Danecek et al, 2011) to calculate the pairwise genomic differentiation for semi-wild and cultivated populations of watermelon.…”
Section: Ratio Of P Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Association mapping has identi ed candidate trait-associated genes in various crops such as Arabidopsis 49 , rice 50 , maize 51 , peach 23 , watermelon 52 and tomato 31 . In this study, we identi ed a total of 239 signi cant signals corresponding to 129 genome loci associated with the 27 assessed agronomic traits.…”
Section: Discussionmentioning
confidence: 99%